1979
DOI: 10.1159/000280267
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Controlled Micturition through Electric Stimulation

Abstract: Historically, man has been aware of bioelectric phenomena for some 4,000 years. Yet it has only been during the last 20 years that technology has advanced to the stage where controlled bladder emptying has become feasible. A great deal of interest followed the introduction of transistor and bladder stimulation via the principle of radio frequency induction. Spinal cord, sacral, and pelvic nerve and direct bladder stimulation have all been attempted. Only direct bladder stimulation in lower motor neuron situati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0
2

Year Published

1982
1982
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(20 citation statements)
references
References 9 publications
1
17
0
2
Order By: Relevance
“…Sacral nerve stimulation (SNS) involves the stimulation of the sacral nerves to modulate the neural reflexes that influence the bladder, urethral sphincter and pelvic floor [1]. In the early 1980s, the work of Schmidt and Tanagho [2,3] showed that electrical stimulation of the sacral nerve root could reduce inappropriate neural activity, thereby inhibiting the overactive detrusor. This pioneering work in neuromodulation led to clinical trials and subsequently to the Food and Drug Administration approval in 1997 of the InterStimÂź system (Medtronic, Inc., Minneapolis, MI, USA) for treating refractory urge incontinence.…”
Section: Introductionmentioning
confidence: 99%
“…Sacral nerve stimulation (SNS) involves the stimulation of the sacral nerves to modulate the neural reflexes that influence the bladder, urethral sphincter and pelvic floor [1]. In the early 1980s, the work of Schmidt and Tanagho [2,3] showed that electrical stimulation of the sacral nerve root could reduce inappropriate neural activity, thereby inhibiting the overactive detrusor. This pioneering work in neuromodulation led to clinical trials and subsequently to the Food and Drug Administration approval in 1997 of the InterStimÂź system (Medtronic, Inc., Minneapolis, MI, USA) for treating refractory urge incontinence.…”
Section: Introductionmentioning
confidence: 99%
“…A clinical program was initiated by the Urology Department of the University of California at San Francisco (UCSF) in 1981, following an extensive laboratory program [2-4, 12, 13]. Since that time, experience has been gathered in the evaluation, surgery, and follow-up of patients presenting with voiding dysfunction and pelvic pain who have been treated with sacral root electrode implants [7][8][9][10][11]. Urinary urgency, frequency, intermittence, and incontinence as well as burning sensations in the urethra or perineum can be effectively treated with neuromodulation in a high percentage of patients.…”
mentioning
confidence: 99%
“…The sacral nerve stimulation or sacral neuromodulation is based on the research by Schmidt and Tanagho (244). This technique stimulates the afferents and thereby probably restores the correct balance between excitatory and inhibitory impulses from and to the pelvic organs at a sacral and supra-sacral level, thus reducing the DO (28,245).…”
Section: 43mentioning
confidence: 99%